Advanced Microengineered Lung Models for Translational Drug Discovery. (September 2018) - Niemeyer, Brian F.; Zhao, Peng; Tuder, Rubin M.; Benam, Kambez H.
Lung diseases impose a significant socioeconomic burden and are a leading cause of morbidity and mortality worldwide. Moreover, respiratory medicine, unlike several other therapeutic areas, faces a disappointingly low number of new approved therapies. This is partly due to lack of reliable in vitro or in vivo models that can reproduce organ-level complexity and pathophysiological responses of human lung. Here, we examine new opportunities in application of recently emerged organ-on-chip technology to model human lung alveolus and small airway in preclinical drug development and biomarker discovery. We also discuss challenges that need to be addressed in coming years to further enhance the physiological and clinical relevance of these microsystems, enable their increased accessibility, and support their leap into personalized medicine.